Training-induced changes in the respiratory compensation point, deoxyhemoglobin break point, and maximal lactate steady state: Evidence of equivalence - Calaine Inglis, E.; Iannetta, D.; Keir, D. A.; Murias, J. M. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To evaluate whether the coherence in the oxygen uptake (V.O2) associated with the respiratory compensation point (RCP), near-infrared spectroscopy-derived muscle deoxyhemoglobin ([HHb]) break point ([HHb]BP), and maximal lactate steady state (MLSS) would persist at the midpoint and endpoint of a 7-month training and racing season. Methods: Eight amateur male cyclists were tested in 3 separate phases over the course of a cycling season (PRE, MID, and POST). Testing at each phase included a ramp-incremental test to exhaustion to determine RCP and [HHb]BP. The PRE and POST phases also included constant power output rides to determine MLSS. Results: Compared with PRE, V.O2 at both RCP and [HHb]BP was greater at MID (delta: RCP 0.23 [0.14] L/min), [HHb]BP 0.33 [0.17] L/min) and POST (delta: RCP 0.21 [0.12], [HHb]BP 0.30 [0.14] L/min)) (P<.05). V.O2 at MLSS also increased from PRE to POST (delta: 0.17 [12] L/min)) (P<.05). V.O2 was not different at RCP, [HHb]BP, and MLSS at PRE (3.74 [0.34], 3.64 [0.40], 3.78 [0.23] L/min)) or POST (3.96 [0.25], 3.95 [0.32], 3.94 [0.18] L/min)) respectively, and RCP (3.98 [0.33] L·min-1) and [HHb]BP (3.97 [0.34] L/min)) were not different at MID (P>.05). PRE-MID and PRE-POST changes in V.O2 associated with RCP, [HHb]BP, and MLSS were strongly correlated (range: r=.85-.90) and demonstrated low mean bias (range=-.09 to .12 L/min)). Conclusions: At all measured time points, V.O2 at RCP, [HHb]BP, and MLSS were not different. Irrespective of phase comparison, direction, or magnitude of V.O2 changes, intraindividual changes between each index were strongly related, indicating that interindividual differences were reflected in the group mean response and that their interrelationships are beyond coincidental.